Tax Governance Using Mobile Payment Online System In Gowa Regency - Muhammad Taufiq Sinaruddin; Haedar Akib; Ismail (International Journal Of Public Policy and Bureaucracy, 2026)
This study aims to describe and analyze regional tax governance through the implementation of Mobile Payment Online System (MPOS) in Gowa Regency, as well as identify the causes of the lack of optimal management of regional taxes, especially restaurant taxes. In addition, this study examines strategic solutions that can be implemented by local governments to increase the effectiveness of tax governance and encourage taxpayer compliance. The research uses a qualitative method with a qualitative descriptive approach. Data collection techniques are carried out through observation, in-depth interviews with relevant informants, and documentation from various official sources. Data analysis is carried out through the process of data collection, condensation, data presentation, and verification to draw valid conclusions. The validity of the data was tested through source triangulation and time triangulation. The results of the study show that the accountability aspect of the Gowa Regency Bapenda is reflected in the disclosure of public information through various digital platforms and official communication media used to support the implementation of MPOS. Transparency is seen through the provision of tax revenue data that can be accessed openly and in real time, thus providing space for the public to monitor the development of regional tax revenues. However, the participation of Bapenda and taxpayers is still not optimal. This can be seen from the low awareness and compliance of some people in fulfilling their tax obligations, as well as the lack of active interaction between local governments and business actors. The collaboration aspect shows that there is cross-sector cooperation between local governments, business actors, and technology providers, although the implementation is not yet fully effective. The conclusions of this study were found to include uneven socialization, the length of time it takes to repair damaged MPOS devices, and weak field supervision. Therefore, a comprehensive strategy is needed in the form of intensifying socialization, improving the quality of supervision, improving the device maintenance system, and enforcing stricter sanctions to increase taxpayer compliance.